(untitled) (Research, Society and Development, 2020)
The aim of the study was to capture the perception of medical students regarding childbirth in a hospital unit of the Unified Health System focusing on the humanization of their praxis in the city of Magé / Rio de Janeiro, where the implementation of the National Humanization Policy is incipient. . The philosophical framework was based on Maurice Merleau-Ponty. It was a qualitative study in which, through an interview based on phenomenology with eighteen medical students, from master’s dissertation data at the Fluminense Federal University, it was possible to analyze their experience in relation to the learning of humanized childbirth. After approval by a specific Research Ethics Committee (opinion number 2,872,462), a phenomenological interview was conducted. The students rated the quality of normal childbirth learning in the health facility as satisfactory; however, they pointed to the difficulty of putting humanization into practice, given the high demand for care. It was not contemplated the humanization that imposes look and communication with the other. The analysis of the perception of others rediscovers the difficulty that the cultural world raises, according to Merleau-Ponty, and thus there is a lapse in the graduation of physician regarding the construction of empathy as an element of humanization. Practical practice in Obstetrics should therefore involve not only theoretical knowledge, but also humanization of childbirth and understanding of sociocultural context of pregnant women.